Alat Pendeteksi Golongan Darah Manusia Berbasis IoT - Farras Nabila; Habibullah Habibullah (Jurnal Teknik Elektro Indonesia, 2022)
This IoT-based human blood type identification tool was created to make data storage easier after testing blood types in big quantities. so that no re-checking is required. A 3.7v lithium battery and a dc boost converter / step-up 5, Arduino UNO, 16x2 LCD, LDR, LED, and WiFi Module ESP8266-01 are among the components used to make a blood type detector. The data from the LDR sensor output is sent via the ESP8266-01 WiFi module, which is connected to the internet network. It will then be transferred to the container page over a WiFi network that is connected to a computer.The data is stored in a PHP database and then shown as a table on the website.